© 2016 Shmoop University, Inc. All rights reserved.
Functions

Functions

Standard Form

A linear equation in standard form is an equation that looks like

ax + by = c

where a, b, and c are real numbers and a and b aren't both zero. But c can be zero if it wants. It's the favorite child, so it gets special privileges.

If only a = 0, the equation can be rewritten to look like this:

y = (some number)

If only b = 0, the equation can be rewritten, too:

x = (some number)

For example, the equation 8y = 3 is equivalent to the equation , which is also in standard form (with b = 1).

Meanwhile, the equation 2x = 4 is equivalent to the equation x = 2, which is also in standard form (with a = 1).

If either a or b is zero, we know how to graph the equation and how to read off an equation from a graph. You probably suspect there will be some cases where it won't be so easy, and neither a nor b will be zero. You suspect right.

Okay, now what if an equation throws us a curveball? Should we sacrifice our bodies and take our base?

If neither a nor b is zero, we can most easily graph the linear equation by finding its intercepts.

Sample Problem

Graph the linear equation x + 4y = 8.

Let's find the intercepts. To find the x-intercept, let y = 0 and solve for x, since the x-intercept will be at a point of the form (something, 0).

x + 4(0) = 8

So x = 8 is the x-intercept.

For the y-intercept, let x = 0 and solve for y.

0 + 4y = 8

And y = 2 is the y-intercept. Sweet, we've tracked down both intercepts. Who needs a or b to be zero? Not us.

Now we can plot the intercepts:

Connect the dots to get the line:


Sample Problem

Write, in standard form, the linear equation graphed below:

The x intercept is at (-1, 0), which means whatever a, b, and c are, our equation looks like this:

a(-1) + b(0) = c

Let's make life easy on ourselves and let a = 1. That's right...we're going to dip this equation in a bucket of A-1 sauce.

1(-1) + b(0) = c
-1 = c

To find b, the remaining coefficient, we look at the y-intercept: y = -2. At that point, x will be 0, and we've already decided that c = -1, so we find:

0 + b(-2) = -1

Therefore, . We now know all the coefficients and can write the equation:

If we want to make things pretty, we can multiply both sides of the equation by 2 and write the resulting equation, which has integer coefficients. If we want to make things really pretty, we can dress the equation up in a sequined ball gown and give it a makeover. Let's start small, though:

2x + y = -2

Sample Problem

Write, in standard form, the linear equation graphed below:

The x intercept is -2, which means whatever a, b, and c are, our standard-form equation is:

a(-2) + b(0) = c

We can let a = 1, so:

-2 = c

To find b we look at the y-intercept, which occurs at (0, 4). And since we've decided c = -2, we find:

0 + b(4) = -2

This means . We now know all the coefficients. Not on a first-name basis, but well enough to get by. We can now write the equation.

To make things pretty, we can multiply both sides of the equation by 2 to get an equivalent equation with integer coefficients:

2xy = -4

Now for that makeover.

People who Shmooped this also Shmooped...